BLOOD ALCOHOL CONCENTRATION AND VIOLENT DEATHS - Paula, Carolina M.C.; Ruzzene, Maria A.M.; Martinis, Bruno S. (Medicina (Ribeirao Preto), 2008)
Brazilian Legislation requests blood alcohol tests only for fatal victims of traffic accidents. In this work we will discuss the need of doing blood alcohol tests for all victims of violent death since abusive use of alcohol represents an important risk factor for all kinds of violent death. The proposal of this study was to analyze the relationship between blood alcohol concentration and the causes of violent death according to gender and age. Blood samples of fatal victims due to violence, from necroscopic examination performed at the Núcleo de Perícias Médico Legal de Ribeirão Preto (NPML-RP) at the Centro de Medicina Legal da Faculdade de Medicina de Ribeirão Preto da Universidade de São Paulo (CEMEL/FMRP/USP) were analyzed in the period from 2002 to 2004. The ethanol analyses were done by gas chromatography using flame ionization detector and using Headspace technique for samples injection. The results showed that higher blood alcohol positivity was observed for victims of accidents, especially for traffic accidents, following by homicides, suicides and undetermined manner of violent deaths. It was observed also that samples collected from male victims were predominant and more than 50% of them presented blood alcohol above the limit established by the Brazilian traffic law which is 0.6 g/l. Results suggests that alcohol abused is highly correlated with violent deaths, mainly traffic accidents involving young males.